Fighting for a name on the ballot: constituency-level analysis of nomination violence in Zambia. Issue 6 (18th August 2018) - Goldring, Edward; Wahman, Michael
ABSTRACT: What factors increase the likelihood of nomination violence? Nomination violence can be an expression of both horizontal conflict, between local political elites, and vertical conflict, between national and local elites. We theorize about factors that may increase the risks of vertical and horizontal conflict and leverage a unique dataset of constituency-level nomination violence obtained from surveys with 464 domestic election observers active in the 2016 Zambian general election. Our statistical analyses show constituencies with an incumbent standing for re-election were more likely to experience nomination violence. Also, contrary to previous research on general election violence, we theorize and find that more rural constituencies had a higher propensity for nomination violence than urban constituencies. Our findings highlight the importance of intra-party power relations and the bargaining relationship between the centre and periphery.